Ecological governance : reappraising law's role in protecting ecosystem functionality / Olivia Woolley. - Woolley, Olivia (Cambridge University Press, 2014)
Ecological degradation has been an object of concern for the international community since the early 1970s, but legal approaches that have been employed to improve the protection of ecosystems have failed to halt this decline. Ecological Governance explores how the law should respond to this rapid global deterioration of ecosystems by examining the foundational scientific and ethical considerations for designing laws that are effective for ecological protection. Based on these analyses, it argues that developed states should prioritise the reduction of the ecological stresses for which they are responsible in decision-making on their future courses. The author also proposes structures for governance and associated legal frameworks that would enable the formulation and implementation of policies for ecological sustainability.